Numerical investigation of natural gas (NG) as low reactivity fuel in a reactivity controlled compression ignition (RCCI) engine model - Firat, Mujdat; Okcu, Mutlu; Altun, Sehmus; Varol, Yasin (Elsevier Sci Ltd, 2023)
Natural Gas (NG) with its high octane number and low C/H ratio is beneficial for reactivity controlled compression ignition (RCCI) engines in controlling the rate of pressure rise and lower the emissions, given that these engines still suffer from these two problems. Therefore, in this study, a detailed 3D combustion model was developed in ANSYS-Forte environment on the scanned image of a real single-cylinder diesel engine for the application of NG to RCCI engines and then validated with the experimental data of the same engine. Afterward, the effect of NG premixed ratio (Rp, 15%, 30% and 45%) on the combustion and emission characteristics of the RCCI engine were analyzed at 20% load and 2400 rpm. Results showed that by increasing the Rp, the heat release rate and cylinder pressure decreased while the ignition delay (ID) period increased. Moreover, NOx and HC emissions were observed to be increased whereas CO and C2H2 emissions tended to be declined as Rp increased. CO emissions were decreased up to 29% when RCCI mode was applied. Also, C2H2 emissions were reduced by about 97% by RCCI compared to CDM. However, engine efficiency started to decrease as Rp increased.
Keywords: Natural gas; RCCI; Numerical analysis; Exhaust emissions